2021
DOI: 10.1038/s41598-021-03123-z
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the zebrafish trrap gene in craniofacial development

Abstract: Trrap (transformation/transcription domain-associated protein) is a component shared by several histone acetyltransferase (HAT) complexes and participates in transcriptional regulation and DNA repair; however, the developmental functions of Trrap in vertebrates are not fully understood. Recently, it has been reported that human patients with genetic mutations in the TRRAP gene show various symptoms, including facial dysmorphisms, microcephaly and global developmental delay. To investigate the physiological fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…By studying this mutant, it has been observed that genetic alterations in the trrap gene have resulted in facial dysmorphisms, microcephaly, and the development of the eyes and pharyngeal arches. 149 Another mutated gene, sin3b, demonstrated a decrease in fitness, size, changes in locomotor behavior, and delayed bone development. 150 In zebrafish, mutants have the potential to be used in drug discovery as disease models.…”
Section: Zebrafish Mutantsmentioning
confidence: 99%
“…By studying this mutant, it has been observed that genetic alterations in the trrap gene have resulted in facial dysmorphisms, microcephaly, and the development of the eyes and pharyngeal arches. 149 Another mutated gene, sin3b, demonstrated a decrease in fitness, size, changes in locomotor behavior, and delayed bone development. 150 In zebrafish, mutants have the potential to be used in drug discovery as disease models.…”
Section: Zebrafish Mutantsmentioning
confidence: 99%